HAK-HAK PEREMPUAN PASCA PERCERAIAN DALAM PERUNDANG-UNDANGAN KELUARGA ISLAM - Hamzanwadi (Prodi. Hukum Ekonomi Syariah, Fakultas Syariah, IAI Hamzanwadi Pancor Lombok Timur, 2022)
One of the implications of divorce is the emergence of rights and obligations that must be fulfilled by husband and wife. This issue has not only been regulated in conventional fiqh, but also received special attention in the positive law in the form of the Marriage Law in the Muslim World. This is evidenced by the inclusion of the problem as one of the thirteen aspects of the Contemporary Muslim Family Law, which according to Tahir Mahmood's research is undergoing renewal. This research is included in the category of qualitative research. Qualitative research is research that produces analytical procedures that do not use statistical analysis procedures or other quantification methods. In conventional fiqh, laws and regulations in Indonesia and even in the world record that the rights of women after divorce are to get Mut'ah, Nafkah, Hadhonah fees and payment of dowry if previously not paid. Keywords: Divorce, women's rights, and regulations.